A Phase 3, Multicenter, Randomized, Controlled Trial to Evaluate Immune Equivalence and Safety of Multidose and Single-dose Formulations of Vi-DT Typhoid Conjugate Vaccine in Healthy Filipino Individuals 6 Months to 45 Years of Age - Josefina Cadorna Carlos; Birkneh Tilahun Tadesse; Charissa Borja-Tabora; Edison Alberto; Michelle C. Ylade; Arijit Sil; Deok Ryun Kim; Hyeon Seon Ahn; Jae Seung Yang; Ji Yeon Lee; Min Soo Kim; Jiwook Park; et al. (Elsevier, 2022)
Summary: Trial Design: Phase 3, randomized, controlled, multicenter, equivalence trial. Methods: Recruitment of participants occurred between 04Februray2020 and 15July2020 at four centers in the Philippines: University of the East - Ramon Magsaysay Memorial Medical Center Inc., Quezon City; University of Philippines Manila - National Institute of Health, Ermita Manila; Asian Hospital and Medical Center, Metro Manila, Philippines Study; and Medical Research Unit, Tropical Disease Foundation, Makati City, Metro Manila, Philippines. Participants: 1800 adults and children 6-months to 45-years of age. Interventions: Participants received a single injection of multidose (MD) or single dose (SD) Vi-DT as test vaccines or meningococcal conjugate vaccine as a comparator. Objective: To evaluate immune equivalence of SD and MD formulations of Vi-DT, and to assess the safety of both formulations compared with comparator vaccine. Outcome Measurement: Blood draw for immunogenicity was performed at baseline prior to vaccine receipt and at four weeks after vaccination for a subset of participants to determine anti-Vi IgG geometric mean titers (GMT) and seroconversion rates. The primary outcome was comparison of anti Vi-IgG seroconversion and GMT between the two formulations of Vi-DT at 4 weeks following vaccine administration. Immune equivalence of MD and SD formulations was confirmed when the two-tailed 95% confidence interval (CI) of the GMT ratio is within [0.67, 1.5] at a two-sided significance level of 0.05. All participants were followed for safety events for six months after vaccine administration. Randomization: Participants were randomized to receive SD Vi-DT, MD Vi-DT, or meningococcal conjugate vaccines in 2.5:2.5:1 allocation ratio. Blinding: Study participants and observers were blinded to treatment assignment. Findings: Immune equivalence of SD (n=252) and MD (n=247) formulations was confirmed by anti-Vi IgG GMT ratio of 1.14 (95%CI: 0.91, 1.43) with respective GMTs in the MD and SD groups of 640.62 IU/mL (95%CI: 546.39, 751.11) and 562.57 IU/mL (95%CI: 478.80, 661.00) (p=0.259). Similarly, anti-Vi IgG seroconversion rate difference between the two formulations of ‒0.43% (95%CI: -4.42, 3.56) confirmed immune equivalence with corresponding seroconversion rates of 98.38% (95%CI: 95.91, 99.37) and 98.81% (95%CI: 96.56, 99.59) in MD and SD Vi-DT formulations, respectively (p=0.722). Both formulations of Vi-DT had a satisfactory safety profile - all five serious adverse events reported during the study were unrelated to the investigational product. Interpretation: The MD and SD formulations of Vi-DT elicited robust and equivalent immune responses following one dose vaccination, and both formulations demonstrated a favorable safety profile. Trial Registration: ClinicalTrials.gov: NCT04204096. Funding: This study was funded by the Bill & Melinda Gates Foundation (OPP 1115556).